E-SAFETY: KEAMANAN DI DUNIA MAYA BAGI PENDIDIK DAN ANAK DIDIK - Niyu Niyu; Herman Purba (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
Based on data from the Child Online Safety Index (COSI), Indonesia occupies the lowest position for online guidance and education related to online activity. This places children and adolescents in a very vulnerable position when interacting in the digital world. With the shift from the learning process to online platforms during the COVID-19 pandemic in 2020, the provision of functions and security in cyberspace (E-Safety) is an important key in maintaining children's interactions when interacting in the digital world. The implementation of E-Safety is in line with the government's program to support the National Digital Literacy Movement (GNLD) and the use of technology in particular to accelerate the transformation of education. This activity was carried out in the form of webinars and workshops for educators as part of digital literacy regarding E-Safety education related to knowledge, skills, and prevention of threats in the digital world. Emphasis on the role of educators as Learner, Advisor, Teacher, and An Identifier is a major part of protecting children and adolescents from dealing with situations and problems mediated by digital media and the internet. Socialization about E-Safety for educators is also equipped with various reference sources that can be used for making E-Safety teaching materials. The result of this activity is an understanding of the importance of E-Safety and its implementation in supporting the resilience of students when interacting in the digital world.